2005
DOI: 10.1159/000088905
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Calcium Lactate to Xylitol Chewing Gum on Remineralization of Enamel Lesions

Abstract: The purpose of the study was to determine whether adding calcium lactate to chewing gum containing xylitol enhances remineralization of enamel surfaces using an early caries lesion model. Enamel slabs were cut from human extracted sound teeth and artificial subsurface lesions created within each. Half the enamel slabs were used as controls and stored in a humidifier while half were mounted into oral appliances worn by 10 volunteers (22–27 years old, 2 males and 8 females) in a three-leg trial, during which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
11
0
6
Order By: Relevance
“…Artificial caries-like lesions were created in human enamel slabs which were subsequently worn by volunteers who used, in a three-leg study, over a period of two weeks, chewing gum containing either xylitol or xylitol + Ca lactate, or did not receive any gum [163]. X-ray spectrometry showed that the xylitol-Ca combination remineralized the lesions more effectively than the xylitol and the no-gum periods.…”
Section: Description Of Individual Remineralization Studiesmentioning
confidence: 99%
“…Artificial caries-like lesions were created in human enamel slabs which were subsequently worn by volunteers who used, in a three-leg study, over a period of two weeks, chewing gum containing either xylitol or xylitol + Ca lactate, or did not receive any gum [163]. X-ray spectrometry showed that the xylitol-Ca combination remineralized the lesions more effectively than the xylitol and the no-gum periods.…”
Section: Description Of Individual Remineralization Studiesmentioning
confidence: 99%
“…Combinations of xylitol with other organic and inorganic compounds in a gum can signifi cantly increase the rate of remineralisation. Such compounds include calcium lactate (Suda et al, 2006) and casein phosphopeptide-amorphous calcium phosphate nanocomplexes (Shen et al, 2001;Reynolds et al, 2003, Iijima et al, 2004. The latter ('Recaldent' formula) are chemically interesting, owing to the presence in the casein phosphopeptide of several phosphoseryl residues that contribute to the stabilisation of nanoclusters of amorphous calcium phosphate in metastable solutions (Reynolds 1998).…”
Section: Gum Products and Remineralisationmentioning
confidence: 99%
“…Hiroshi Sano 1) , Syozi Nakashima 2) , Yupin Songpaisan 3) and Prathip Phantumvanit Original combination with fluoride in topical oral products, such as toothpaste, is not clear with respect to the remineralization process.…”
Section: Effect Of a Xylitol And Fluoride Containing Toothpaste On Thmentioning
confidence: 99%
“…The caries inhibiting effect of xylitol has so far been demonstrated by its ability to inhibit the growth and metabolism of the mutans group of streptococci and dental plaque. Xylitol containing products including toothpaste, gum and mouth rinse have shown anticaries properties (1)(2)(3)(4), possibly due to the effects of xylitol on plaque formation, microorganisms, salivary secretion and composition, and on enamel lesions.…”
Section: Introductionmentioning
confidence: 99%